Tannic Acid-Steeped Corn Grain Modulates in vitro Ruminal Fermentation Pattern and Microbial Metabolic Pathways - Zhao, F. F.; Zhang, X. Z.; Zhang, Y.; Elmhadi, Mawda; Qin, Y. Y.; Sun, H.; Zhang, H.; Wang, M. Z.; Wang, H. R. (Frontiers in Veterinary Science, 2021)
This study investigated the effects of tannic acid (TA)-treated corn on changes in ruminal fermentation characteristics and the composition of the ruminal bacterial community in vitro. Ruminal fluid was obtained from three rumen-fistulated goats fed a 60:40 (forage/concentrate) diet. The batch cultures consisted of 25 ml of strained rumen fluid in 25 ml of an anaerobic buffer containing 0.56 g of ground corn, 0.24 g of soybean meal, 0.10 g of alfalfa, and 0.10 g of oat grass. Ground corn (2 mm) was steeped in an equal quantity (i.e., in a ratio of 1:1, w/v) of water alone (Con), 15 (TA15), 25 (TA25), and 35 g/l (TA35) TA solution for 12 h. After incubation for 24 h, TA-treated corn linearly increased (P <0.05) ruminal pH and the molar proportion of acetate, but linearly reduced (P <0.05) total volatile fatty acids and the molar proportion of butyrate compared with the Con treatment. Illumina MiSeq sequencing was used to investigate the profile changes of the ruminal microbes. A principal coordinates analysis plot based on weighted UniFrac values revealed that the structure of the ruminal bacterial communities in the control group was different from that of the TA-treated corn groups. The results of changes in the rumen bacterial communities showed that TA-treated corn linearly enriched (P <0.05) Rikenellaceae_RC9_gut_group, but linearly reduced (P <0.05) Ruminococcaceae_NK4A214_group, Ruminococcus_2, and unclassified_o__Clostridiales. Functional prediction of ruminal microbiota revealed that the TA-treated corn linearly decreased ruminal microbiota function of utilizing starch through pyruvate metabolism. In conclusion, TA-treated corn can modulate the rumen fermentation characteristics, microbial composition, and metabolic pathways, which may be potentially useful for preventing the occurrence of ruminal acidosis.